Perancangan Dan Implementasi Sistem Akuntansi Pada Mama Kitchen - Hendi Hendi; Yenny Susanti (Universitas Internasional Batam, 2021)
Mama Kitchen is a business in the form of food stand that sells various kinds of food. Until now, Mama Kitchen does not have an accounting system. Mama Kitchen are still using manual recording methods. The purpose of this work is to make accounting records easier for the owner. The research was done by interviewing the owner and employees, and direct survey to location in order to know clearly about their daily activities. System will be designed according to Mama Kitchen’s needs. The result of implementation of this research is an accounting system that can produce financial reports. By having a system, owner can easily see the business profits accurately and ease owners in making decision about their business.